Mobile payment and e-wallet adoption in emerging economies: a systematic literature review / Faten Aisyah Ahmad Ramli and Muhammad Iskandar Hamzah - Ahmad Ramli, Faten Aisyah; Hamzah, Muhammad Iskandar (Universiti Teknologi MARA, 2021)
Against the backdrop of greater smartphone and internet penetration across the emerging markets, electronic wallet (e-wallet) has emerged as a reliable and well-known digital payment method. The main purpose of this paper is to review the growing volume of studies on e-wallet adoption in this region. E-wallet is widely used worldwide, but it has yet to become mainstream in developing countries, including Malaysia. Hence, scholars have conducted numerous studies on e-wallet use, but there seems to be a lack of consensus on the predictors influencing its adoption. This study examines these publications to analyze the potential research gaps, offer a multi-stakeholder eco-system framework and make recommendations for future research. We retrieved scholarly articles on E-Wallet adoption published from 2016-2021 through the Google Scholar and Scopus database. After the screening process in which some papers were excluded, 77 previous studies were reviewed regarding the methodology, findings and adaptation of theories/models. Considering that a large portion of the studies are grounded based on the technology acceptance framework and typically involved drivers and enablers, we call for a distinct approach that draws in other factors into the equation. For instance, future research may divulge the inhibitors to E-wallet adoption and incorporate the external environment and consumer psychological factors as potential predictors.